Chemical composition and antibacterial activities of Capparis spinosa essential oils from Algeria - halima Benachour; Messaoud Ramdani; Takia Lograda; Pierre Chalard; Gilles figueredo (Society for Indonesian Biodiversity, 2020)
Abstract. Benachour H, Ramdani M, Lograda T, Chalard P, Figueredo J. 2020. Chemical composition and antibacterial activities of Capparis spinosa essential oils from Algeria. Biodiversitas 21: 161-169. The essential oils of Capparis spinosa L. collected from six locations in Algeria were obtained by hydro-distillation. The chemical composition of oils was performed by GC-MS. The disc diffusion method is applied for the antibacterial activity. The extraction produced low yield (0.03%). The result of chromatographic analysis (GC/MS) leads to the identification of 33 components; palmitic acid (38.19%), nonanal-n (12.61%), cymene-2,5-dimethoxy-para (8.94%) and octacosane (5.49%) were the major components of these oils. The result of cluster analysis based on essential oils constituents showed the presence of three chemotypes,i.e., the chemotype of Nonanal-n-Cymen 2,5 dimethoxy para-Dodecanal, the chemotype of Nonanal-n-Hexadecanoic acid-tetracosane and the chemotype Tetracosane-n-pentyl furane-2-octacosane. In-vitro antimicrobial activity of caper oils against nine bacterial species showed that the oils have no activity against E. coli and have modest activities against eight other bacterial species tested; however, the desirability test shows that the oils used were not effective on the bacteria tested.